Advanced photodegradation and antimicrobial performance: a comparative study of Al/Ag-Co-doped ZnO synthesis via laser assist chemical bath - Zyoud, Samer H.; Ashames, Akram; Zyoud, Ahed H.; Prasad, Anupama R; Abdullah, Che Azurahanim Che; Zyoud, Shaher H.; Yahia, Ibrahim S.; Makhadmeh, Ghaseb N.; Khalid, Awais; Qamhieh, Naser; Zahran, Heba Y.; Muhammad, Sani; et al. (Elsevier Ltd, 2024)
This study utilizes a novel laser-assisted chemical bath synthesis (LACBS) approach to dope zinc oxide (ZnO) nanostructures with aluminum (Al) and silver (Ag), examining enhancements in photocatalytic and antimicrobial capabilities. The configurations tested include undoped ZnO, singly-doped ZnO(0.05) and ZnO(0.05), and co-doped ZnO:[Ag(0.025), Al(0.025)]. X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses reveal shifts in lattice orientations and novel morphologies such as crumpled nano-flakes and interlocked flower-like formations. UV–visible spectroscopy results show a reduction in optical band gaps from 3.39 eV in undoped ZnO to 2.89 eV in co-doped samples. Photocatalytic activity testing under UV light reveals that undoped ZnO reaches a 68 % degradation efficiency of methylene blue over 10 min, while co-doped ZnO exhibits a superior 78.93 % efficiency under blue laser illumination. Antimicrobial assays indicate that co-doped ZnO inhibits Escherichia coli and Klebsiella pneumonia growth with zones of inhibition up to 40 mm, significantly larger than those observed with singly-doped or undoped samples. The integration of Al and Ag significantly enhances the crystalline structure, reduces the optical band gap by up to 0.50 eV, and increases both photocatalytic and antimicrobial effectiveness, marking substantial progress in the functional applications of ZnO nanostructures.